The Effect of Online Games on Changes in Student Behavior in Middle Schools - Nurharsya Khaer Hanafie; Bakhtiar Bakhtiar; Darmawati Darmawati (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2022)
The Effect of Online Games on Changes in Student Behavior in Junior High Schools The approach used in this study is an associative approach with quantitative research. The data collection techniques used observation, questionnaires/questionnaires and documentation. While the data analysis used simple linear regression test, Product Moment Correlation test, partial test (t), and the determinant coefficient. The results of this study indicate that: (1) Online games affect changes in student behavior in junior high schools, this is indicated by the results of the t-test analysis or partial test. The t-test or partial test is a statistic used to test the truth or falsity of the null hypothesis. So the results of statistical test analysis are known that there is a significant influence between the online game variable (X) and the student behavior change variable (Y). This means that the higher the intensity of playing online games played by students, the changes in student behavior are increasing/bad. The indicator factors for online game variables are the most dominant influencing changes in student behavior. namely online games are only used unilaterally, not balanced with valuable activities, so that they only have a negative impact and cause bad effects for students. Keywords: Effect Online Games, Students Behavior, Online Games